Experimental evidence for curcumin and its analogs for management of diabetes mellitus and its associated complications - Rivera-Mancía, Susana; Lozada-García, María Concepción; Pedraza-Chaverri, José (European journal of pharmacology, 2015)
Diabetes mellitus is a serious world health problem and one of the most studied diseases; a major concern about its treatment is that β-cell mass and functionality is hard to restore. In addition, it is frequently associated with severe complications, such as diabetic nephropathy and cardiomyopathy. The anti-inflammatory, anti-oxidative and anti-apoptotic properties of curcumin have made it a promising molecule for the treatment of this pathology; however, its solubility and bioavailability problems are still the subject of multiple studies. To cope with those difficulties, several approaches have been evaluated, such as the development of pharmaceutical formulations and curcumin analogs. This review discusses some of the studied therapeutic targets for curcumin in diabetes as well as the structural characteristics and targets of its analogs. The shortening of the central seven-carbon chain of curcumin has given rise to compounds without glucose-lowering effects but potentially useful for the treatment of diabetes complications; whereas preserving this chain retains the glucose-lowering properties. Most of the analogs discussed here have been recently synthesized and tested in animal models of type 1 diabetes; more studies in models of type 2 diabetes are needed.